HUBUNGAN ANTARA UKURAN SMARTPHONE DENGAN KEJADIAN PARESTHESIA DI PALMAR AKIBAT PENYEMPITAN TEROWONGAN CARPAL PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA - Ni Kadek Yuni Fridayani; Ni Luh Nopi Andayani; Ni Wayan Tianing (Bachelor of Physiotherapy and Physiotherapy Profession Study Program, Faculty of Medicine, Udayana University in collaboration with Indonesian Physiotherapy Association (IPA), 2018)
ABSTRACT Using smartphone in different size can give different effectwhilehold and swipe smartphone so, this study was to analyze the relationship between the size of smartphone and paresthesia in palmar caused by constriction at carpal tunnel. Cross sectional analytic study with subjects were 109 students of Medical Faculty Udayana University. The sample of this study is the students who scored SAS (Smartphone Addiction Scale) ? 84, inclusion and exclusion. The participants asked to use a smartphone for 30 minutes, one-handed while maintaining comfortable sitting postures on a chair. The result showed no significant correlation between the size of smartphone and paresthesia in palmar caused by constriction at carpal tunnel and also was found that smartphone large more cause paresthesia in palmar (46,5%) than small category (39,5%) and medium (14,0%). Subjects were more fatigue in thumb and finger after using smartphone than paresthesia. So, the use of smartphones with large category can caused paresthesia and continued with musculoskeletal problem especially in thumb. Keywords: size of smartphone, paresthesia, constriction at carpal tunnel